2020
DOI: 10.1111/apt.15935
|View full text |Cite
|
Sign up to set email alerts
|

Review article: the impact of liver‐directed therapies on the atherogenic risk profile in non‐alcoholic steatohepatitis

Abstract: Summary Background Patients with non‐alcoholic fatty liver disease (NAFLD), the most common cause of chronic liver disease, are at higher risk of cardiovascular disease (CVD) and associated mortality. Therefore, it is important to understand how new therapies for non‐alcoholic steatohepatitis (NASH) may impact CVD risk factors in these patients. Aims To summarise the effects of drug therapies on lipid and lipoprotein levels in patients with NASH and provide insight into the potential mechanisms for the observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 170 publications
(357 reference statements)
0
5
0
Order By: Relevance
“…However, its clinical applications may be limited by various side effects, including fluid retention and weight gain. [ 34 ] We found that pharmacologic inhibition of the expression of ACSL4 by administering abemaciclib at 30 mg/kg per day significantly suppressed body weights and improved NASH‐associated pathological features, including hepatic steatosis and fibrosis. In 2017, Abemaciclib was approved by the United States Food and Drug Administration (FDA) to treat hormone receptor‐positive and HER2‐negative breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…However, its clinical applications may be limited by various side effects, including fluid retention and weight gain. [ 34 ] We found that pharmacologic inhibition of the expression of ACSL4 by administering abemaciclib at 30 mg/kg per day significantly suppressed body weights and improved NASH‐associated pathological features, including hepatic steatosis and fibrosis. In 2017, Abemaciclib was approved by the United States Food and Drug Administration (FDA) to treat hormone receptor‐positive and HER2‐negative breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…FXR regulates bile acid synthesis by suppressing key enzymes in the biosynthetic pathway [14]. A number of therapies are under investigation for the treatment of NAFLD and NASH [5,15,16], however, no pharmacological agent is currently approved. FXR agonists are in clinical development for the treatment of NASH as well as other chronic liver diseases.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, there are novel therapies under investigation (20)(21)(22)(23) alone or in combination (24,25): Glucagon-Like Peptide 1(GLP1) Agonist, Sodium-Glucose Cotransporter-2 (SGLT2) Inhibitors, Peroxisome Proliferator-Activated-Receptor (PPAR) agonist, Caspase inhibitors, Acetyl-CoA inhibitors, Apoptosis Signal-Regulating Kinase 1 (ASK1) Inhibitors, and Farnesoid X Receptor (FXR) agonists. Some of these therapies increase serum lipids and the combination of statins with them will mitigate this effect (26). The results of phase 3 trials with these drugs will shed light on future treatment of NASH/NAFLD.…”
Section: Pharmacotherapy In Nash/nafldmentioning
confidence: 99%